- #1

Ben-CS

Solve the following differential equation:

*y*′′′ =

*y*

- Thread starter Ben-CS
- Start date

- #1

Ben-CS

Solve the following differential equation:

- #2

- 508

- 0

y(t) = a*exp(b*t) where b^3 = 1.

- #3

dg

y(x)=c1*exp(q1*x)+c2*exp(q2*x)+c3*exp(q3*x)

where c1, c2 and c3 are (complex) constant that can be fixed by initial conditions and

q1=1

q2=(-1+i*sqrt(3))/2

q3=(-1-i*sqrt(3))/2

This can be re-written in the real field as

y(x)=exp(x)* c1 + A*exp(-x/2)*cos(sqrt(3)*x+B) )

where A and B are new constants depending on c2 and c3 only.

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 2K

- Last Post

- Replies
- 8

- Views
- 1K

- Last Post

- Replies
- 30

- Views
- 5K

- Replies
- 2

- Views
- 2K

- Replies
- 5

- Views
- 14K

- Replies
- 5

- Views
- 7K

- Replies
- 7

- Views
- 2K

- Replies
- 2

- Views
- 2K

- Replies
- 2

- Views
- 647